Aktivitas Antijamur Fraksi N-Heksana Kulit Buah Citrus sinensis (L.) Osbeck - Melzi Octaviani; Wiwin Suryani; Nofri Hendri Sandi (Universitas Wahid Hasyim Semarang, 2024)
The sweet orange (Citrus sinensis (L.) Osbeck) is a fruit that is loved by all walks of life because of its sweet taste. The flesh part of the fruit is consumed, while the fruit peel is discarded. However, the fruit peel also contains secondary metabolites, which have various biological activities. The peel of this sweet orange fruit contains secondary metabolites of alkaloids, flavonoids, phenolics, steroids, and terpenoids. This study aims to determine the antifungal activity of the n-hexane fraction against Trichophyton mentagrophytes and Candida albicans using the disc diffusion method and the Minimum Inhibitory Concentration (MIC). The results of measuring the diameter of the inhibition zone formed on the fungus Trichophyton mentagrophytes at a concentration of 50; 25; 12.5; 6.25; 3.125 and 1.5625% w/v, respectively 12.29±0.08; 11.14±0.12; 9.54±0.17; 7.01±0.12; 6.19±0.03; 6.06 ± 0.03 mm, with a MIC of 1.5625 %. Results of measuring the diameter of the inhibition zone formed against Candida albicans fungi respectively 9.97 ± 0.02; 9.05±0.18; 8.32±0.38; 7.09±0.07; 6.00±0.00; 6.00±0.00 mm, with a MIC of 6.25%. The results of data analysis using one-way ANOVA statistics showed that there was a significant difference (p<0.05) between variations in the concentration of the test fraction with positive control and negative control. Based on the research that has been carried out, it can be concluded that the n-hexane fraction of sweet orange peel has activity in inhibiting the growth of the test fungus, with the best antibacterial activity at a concentration of 50% w/v.